2012
DOI: 10.1371/journal.pone.0045182
|View full text |Cite
|
Sign up to set email alerts
|

Idebenone Protects against Retinal Damage and Loss of Vision in a Mouse Model of Leber’s Hereditary Optic Neuropathy

Abstract: Leber’s hereditary optic neuropathy (LHON) is an inherited disease caused by mutations in complex I of the mitochondrial respiratory chain. The disease is characterized by loss of central vision due to retinal ganglion cell (RGC) dysfunction and optic nerve atrophy. Despite progress towards a better understanding of the disease, no therapeutic treatment is currently approved for this devastating disease. Idebenone, a short-chain benzoquinone, has shown promising evidence of efficacy in protecting vision loss a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 50 publications
(71 reference statements)
5
85
2
1
Order By: Relevance
“…In this model, idebenone protected against the loss of retinal ganglion cells, reduction in retinal thickness and gliosis. Furthermore, consistent with this protection of retinal integrity, idebenone restored the functional loss of vision in this disease model [16]. After a 3 months treatment, we observed a slightly increase of VA and an improvement in contrast sensitivity in our patients.…”
Section: Discussionsupporting
confidence: 88%
“…In this model, idebenone protected against the loss of retinal ganglion cells, reduction in retinal thickness and gliosis. Furthermore, consistent with this protection of retinal integrity, idebenone restored the functional loss of vision in this disease model [16]. After a 3 months treatment, we observed a slightly increase of VA and an improvement in contrast sensitivity in our patients.…”
Section: Discussionsupporting
confidence: 88%
“…However, many in vivo studies showed much potential of idebenone against oxidative stress in the eye [12,52,53] and other organs [13,21,54]. Antioxidants already are a major pillar of AMD therapy, but they are still not fully satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its balanced lipophilicity (log D = 3.9) [44], idebenone can repeatedly cross membranes, such as the mitochondrial membranes, and can be re-activated by cytoplasmic NQO1, which allows idebenone to re-establish ATP levels in cells with impaired complex I function. The observation that idebenone protects the retinal ganglion cell line RGC5 against mitochondrial complex I inhibition supports this model [46]. This mechanism of action also explains why idebenone cannot be substituted by other antioxidants or by CoQ 10 , which is exclusively located within membranes.…”
Section: Pharmacodynamicsmentioning
confidence: 52%
“…Importantly, the authors also demonstrated that orally administered idebenone penetrated rapidly into the eye fluids within minutes and most importantly also protected against loss of vision in this animal model [46].…”
Section: Pharmacodynamicsmentioning
confidence: 80%